2018
DOI: 10.5430/jnep.v8n6p66
|View full text |Cite
|
Sign up to set email alerts
|

“They can crush you”: Nursing students’ experiences of bullying and the role of faculty

Abstract: This paper will explore the faculty role when nursing students experience bullying, and what teaching practices best support student confidence and learning. Failure to address the issue of bullying in nursing education contributes to bullying in the profession, and creates an atmosphere of distrust between students and faculty. Nursing students have reported that faculty sometimes behave in bullying ways or are ill-prepared to address bullying as it occurs. Faculty may contribute to bullying unknowingly, as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…In another study conducted in United States (US), Smith, et al [24] confirmed that nursing students experience various forms of bullying behaviors in clinical setting. In contrast, recent research of Seibel and Fehr [3] emphasized that different types of bullying can be happened in class or clinical settings within and between student and faculty groups.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In another study conducted in United States (US), Smith, et al [24] confirmed that nursing students experience various forms of bullying behaviors in clinical setting. In contrast, recent research of Seibel and Fehr [3] emphasized that different types of bullying can be happened in class or clinical settings within and between student and faculty groups.…”
Section: Discussionmentioning
confidence: 90%
“…Abd-Elrahman [22] revealed that 87.6% (N=709) of Egyptians' student nurses are experiencing bullying behaviors. Accordingly, Seibel and Fehr [3] recognized bullying behaviors as common complaints among nursing students and routine experiences in academia and clinical setting. In this aspect, Smith, et al [24] illustrated that the extent of bullying behaviors experienced by nursing students is unclear as percentages range among studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations